Muslims' Day-to-Day Handling of Property and the Adherence to Islamic Norms: A Systematic Review of Studies for Western Europe - Müssig, Stephanie (Journal of Muslims in Europe, 2015)
The aim of this work is to answer the question: "What role do Islamic norms play in property-related attitudes and behaviour of Muslims living in Western European societies?" To this end, a systematic review of electronic journal databases was undertaken to identify academic works published on the matter up to August 2013. Twenty relevant papers were identified, all of which contained original data. The empirical results of the studies show that Muslims in Western Europe incorporate Islamic norms in their decisions in everyday situations and secular life.
Created from Fastlane, Scopus look-up
Keywords: attitudes; behaviour; economy; Islam; Muslim; property; religion; religious norms